Finite Element Modelling for Fracture of Multilayer Fibrous Networks - Chung, S. M; Theng, Koh Ching (International Journal of Integrated Engineering, 2020)
Tissue engineering involves three-dimensional scaffolds to support cell culture activities and provide mechanical support. One of the potential scaffolds used in tissue engineering is an electrospun scaffold consisting fibres ranging from nano- to micrometer scales deposited on layer stack. The finite element models have been used to study the in-plane deformation of two-dimensional single layer fibrous networks and without considers out-of-plane deformation. While the existing study focuses on two-dimensional study, the out-of-plane deformation of layer structured of electrospun scaffolds through the scaffolds thickness has not been studied. In this study, three-dimensional finite element model was constructed to investigate the fracture of multilayer fibrous networks. The three-dimensional results were compared with the fracture on two-dimensional single layer fibrous network. The result shows that these two models had identical fracture behaviour and similar deformation at the crack-tip region, where the fibres are rearranged and reoriented with similar stress distribution. The work here concludes that two-dimensional single layer fibrous network model is a simple yet effective model for the study of homogeneous fibrous networks.